Facile solid-phase synthesis of head-side chain cyclothiodepsipeptides through a cyclative cleavage from MeDbz-resin. Issue 28 (12th July 2017) - Acosta, Gerardo A.; Royo, Miriam; de la Torre, Beatriz G.; Albericio, Fernando
Graphical abstract: Highlights: Efficient solid-phase synthesis of cyclothiodepsipeptides. MeDbz linker as a safety catch linker. High purity of final cyclic peptides thanks to the cyclative cleavage. Abstract: Head to side-chain cyclothiodepsipeptides were conveniently prepared through a cyclative cleavage using the MeDbz linker. Briefly, the peptide sequence was elongated on a MeDbz-Gly-ChemMatrix resin and reacted with 4-nitrophenyl chloroformate, followed by treatment with DIEA to render an activated cyclic N -acyl- N′ -methylurea-resin. Removal of the Cys protecting group and further treatment with DIEA allowed the formation of the thiolactone with the concomitant release of the cyclic peptide from the resin.